EPIDEMIOLOGI UNTUK 'QUALITY ASSESSMENT' PELAYANAN KESEHATAN GIGI MULUT - Zaura Anggraeni Matram (Faculty of Dentistry, Universitas Indonesia, 2015)
The need for quality assessment and assurance in health and oral health becomes an issue of major concern in Indonesia, particularly in relation to the significant decrease of available resources due to the persistence economical crisis. Financial and socioeconomical impacts have led to the need for low cost - high quality accessible oral care. Dentists are ultimately responsibel for the quality of care performed in Public Helath Center (Puskesmas) especially for School and Community Dental Programmes often performed by various type of health manpower such as dental nurses and cadres (volunteers). In this paper, emphasis has been placed on two epidemiological models to assess the quality of outcomes of service as well as management control for quality assessment in School Dental Programme. Respectively epidemiological moderls were developed for assessing the effectiveness of oral health education and simple oral prophylaxis carried out the School Dental Programme (known as UKGS). With these epidemiological approaches, it is hope dentists will gain increase appreciation for qualitative assessment quality of care instead of just quantitavely meeting the target that many health administrations use it to indicate success.